2017
DOI: 10.3802/jgo.2017.28.e65
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with survival after relapse in patients with low-risk endometrial cancer treated with surgery alone

Abstract: ObjectiveTo determine factors influencing overall survival following recurrence (OSFR) in women with low-risk endometrial cancer (EC) treated with surgery alone.MethodsA multicenter, retrospective department database review was performed to identify patients with recurrent “low-risk EC” (patients having less than 50% myometrial invasion [MMI] with grade 1 or 2 endometrioid EC) at 10 gynecologic oncology centers in Turkey. Demographic, clinicopathological, and survival data were collected.ResultsWe identified 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…It should be emphasized that low-risk endometrial cancer patients may be qualified as high-intermediate risk with the contribution of age (>70 years), grade of the tumor (grade 2), and/or positive lymphovascular space invasion status 6. Aristizabal et al33 reported a retrospective analysis of 518 patients (198 lymphovascular space invasion-positive tumors and 310 lymphovascular space invasion-negative tumors) with stage I endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be emphasized that low-risk endometrial cancer patients may be qualified as high-intermediate risk with the contribution of age (>70 years), grade of the tumor (grade 2), and/or positive lymphovascular space invasion status 6. Aristizabal et al33 reported a retrospective analysis of 518 patients (198 lymphovascular space invasion-positive tumors and 310 lymphovascular space invasion-negative tumors) with stage I endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Among women with endometrioid endometrial cancer, low-risk endometrial cancer represents the largest group,5 and the rate of low-risk endometrial cancer has been reported as 40.5% among all endometrioid endometrial cancers in Turkey 6. Low-risk endometrial cancer has a good outcome, particularly in young women, and the 5-year survival rate has been reported to be 96% 7.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, those studies were not different from the current data that half of the recurrences are vaginal, followed by peritoneal, hematogenous, and lymphatic spread [16]. A significant portion of the recurrences in patients with endometrioid EC occur within the first 2 years (37.5% of patients recurred within the first year, 54.2% within the second year, and 8.3% within the third year) [10].…”
Section: Discussionmentioning
confidence: 71%
“…Patient data were extracted from five institutions with maintained EC databases. These five centers (all of them participated in our previous multicenter studies on EC) were chosen because of their high volume of endometrioid EC presentations. Some of the patients in this study were within the context of one of our previous studies .…”
Section: Methodsmentioning
confidence: 99%
“…The date of diagnosis, adjuvant treatment modality (radiotherapy, chemoradiotherapy or chemotherapy), recurrence (if applicable), time to recurrence (TTR) (as a continuous variable in months, if applicable), site of recurrence (locoregional, retroperitoneal, distant), length of follow up and survivals were noted. Data were collected from centers with an online standardized form …”
Section: Methodsmentioning
confidence: 99%